1979
DOI: 10.1002/jsfa.2740300202
|View full text |Cite
|
Sign up to set email alerts
|

Changes during ensilage in the nitrogenous components of fresh and additive treated ryegrass and lucerne

Abstract: The changes in the major nitrogenous components of herbage during the ensilage of lucerne and Italian ryegrass, with and without the addition of 85 % formic acid and 40% formaldehyde at the rates of 3.2 and 7.4 g kg-l fresh herbage respectively, were studied. Both herbages were of similar amino-N composition except for asparagine which was about 10% of total nitrogen (TN) in lucerne and only 0.2% of TN in Italian ryegrass. After 90 days ensiling about 90% of the sum of protein-, peptide-, amino-and amide-N was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
19
0
4

Year Published

1981
1981
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 24 publications
11
19
0
4
Order By: Relevance
“…in studies quoted above, these amino acids showed a net de-crease in silage. A pattern observed here and also documented by other workers (Ohshima et al 1979;Merchen and Satter 1983) (Gill and Ulyatt 1977) or where casein was infused postruminally in lambs (Egan 1965;Papas et al 1974) food intake was stimulated. Egan and Rogers (1978) have also reported reduction in food intake by lambs experiencing a postruminal imbalance of amino acids.…”
Section: Discussionsupporting
confidence: 90%
“…in studies quoted above, these amino acids showed a net de-crease in silage. A pattern observed here and also documented by other workers (Ohshima et al 1979;Merchen and Satter 1983) (Gill and Ulyatt 1977) or where casein was infused postruminally in lambs (Egan 1965;Papas et al 1974) food intake was stimulated. Egan and Rogers (1978) have also reported reduction in food intake by lambs experiencing a postruminal imbalance of amino acids.…”
Section: Discussionsupporting
confidence: 90%
“…13 Bacterial inoculants and treatment of silages with chemicals can also limit protein breakdown and the catabolism of amino acids in grass silages. 14,15 Species containing tannin, such as sainfoin or sulla (Hedysarum coronarium L), undergo less protein degradation during ensiling than species that do not contain tannin. 8 These compounds react with proteins making them resistant to breakdown by proteases both in the silo and in the rumen.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of crude protein is not modified with the ensiling process, although different proportions of nitrogen fractions may be altered. It is known that fermentation causes changes in the composition of nitrogen fractions, reducing the true protein content and increasing the content of free amino acid, or products from the breakdown of these of amino acids, including ammonia, CO 2 and amines (Ohshima & McDonald, 1979). Thus, the low nitrogen content of silages is a limiting factor for the use of forage of these genotypes mainly for animals with high nutritional requirements.…”
Section: Resultsmentioning
confidence: 99%